Identificação de indicadores de sustentabilidade para a aplicação e monitoramento da Política Nacional de Agroecologia e Produção Orgânica (PNAPO) e do Plano Estadual de Agroecologia e Produção Orgânica do Estado de São Paulo (PLEAPO-SP) - Moraes, Lyvia Camargo de (Universidade Federal de São Carlos, 2025)
Agroecology and organic production have been consolidating as fundamental strategies for promoting sustainability, food security, and sustainable rural development in Brazil, strengthened through public policies such as the National Policy on Agroecology and Organic Production (PNAPO) and the State Plan for Agroecology and Organic Production (PLEAPO). In this context, the objective of this study was to identify sustainability indicators that can be used to monitor the implementation of the PNAPO and the PLEAPO. The methodology adopted consisted of bibliographic and documentary research, based on the analysis of scientific articles, official documents, and governmental plans related to agroecology, organic production, and sustainability indicators. The results show that, although guidelines and plans have been established, there are still weaknesses in the standardized use of indicators for policy monitoring, which makes the systematic evaluation of their effectiveness difficult. It is concluded that strengthening monitoring systems through the adoption of clearer and more integrated indicators is essential for consolidating the PNAPO and the PLEAPO and for achieving the Sustainable Development Goals.
Identification of sustainability indicators for the implementation and monitoring of the National Policy on Agroecology and Organic Production (PNAPO) and the State Plan for Agroecology and Organic Production of the State of São Paulo (PLEAPO-SP)
Keywords: Agroecologia; Políticas públicas; Indicadores de sustentabilidade; Agroecology; Public policies; Sustainability indicators; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::POLITICA E PLANEJAMENTO GOVERNAMENTAIS; 12. Consumo e Produção Responsáveis; 2. Fome Zero e Agricultura Sustentável; 10. Redução das Desigualdades